Effects of oil-dispersed phase composition and selected polysaccharides on the physical properties and stability of soybean-palm kernel olein blend oil-in-water emulsions model system - Norhayati Ibrahim (Selangor: Universiti Putra Malaysia, 2013)
An oil-in-water (0/W) emulsion is a system that consists of oil droplets dispersed in an aqueous continuous phase. Soybean oil (SBO) is commonly being used as oildispersed phases in many 0/W-based food products. The products sometimes exhibit poor physical properties and stability against temperature fluctuations that can be attributed to a high unsaturation degree of SBO. These problems can be reduced by blending of SBO with more saturated oils such as palm kernel olein(PKO).